Health on equal terms? - Västra Götaland, 2016 - Public Health Agency of Sweden (Public Health Agency of Sweden, 2016)
The survey "Health on equal terms?" is a national survey, conducted every year since 2004. The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2016, Göteborgs Stad ordered an additional sample.

The population consisted of all people in the municipality of Gothenburg aged 16-84 and the additional sample ordered by Göteborgs Stad consisted of 4984 persons. The total sample, i.e. the additional sample and the individuals from Gothenburg in the national sample was 6200 people.

A total of 2693 individuals answered the questionnaire, representing a response rate of 43,5 percent. The number of webb responses was 753 or 28,0 percent of the respondents.

The Public Health Agency designed the questions in the questionnaire which consisted of 62 numbered questions. Several questions had sub-questions, which resulted in a total of 93 questions. The questions in the questionnaire dealt with subjects such as health, lifestyle, economical conditions, work and employment as well as security and social relations. In addition to the variables collected through the questionnaire a number of variables were retrieved from registers.

Purpose:

The aim of the national survey is to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Göteborgs Stad is to investigate the health in the population in Gothenburg.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2016 beställde Göteborgs Stad ett tilläggsurval.

Populationen utgjordes av samtliga personer i Göteborgs kommun i åldern 16-84 år och Göteborgs tilläggsurval bestod av 4984 personer. Det totala antalet urvalspersoner, dvs. tilläggsurvalet inklusive urvalspersonerna från Göteborg i det nationella urvalet var 6200 personer.

Totalt svarade 2693 personer på frågeblanketten, vilket var 43,5 procent av urvalet. Antalet webbsvar var 753 stycken eller 28,0 procent av de svarande.

Folkhälsomyndigheten utformade frågorna i frågeblanketten vilken bestod av 62 numrerade frågor. Flera av frågorna hade delfrågor vilket resulterade i sammanlagt 93 frågor. Frågorna i frågeblanketten handlade bland annat om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer. Utöver de variabler som samlades in via frågeblanketten hämtades ett antal variabler från register.

Syfte:

Syftet med den nationella undersökningen är att ta reda på hur Sveriges befolkning mår och lever och även att följa upp den nya folkhälsopolitiken. Syftet med urvalet för Göteborgs Stad är att ta reda på hur befolkningen i Göteborg mår och lever.
Hälsa på lika villkor? - Västra Götaland, 2016 - Hälsa på lika villkor, Västra Götaland, 2016
Keywords: Health Services; Hälso- och sjukvård; Body Constitution; Kroppskonstitution; Hearing; Hörsel; Life Style; Livsstil; Pathological Conditions, Signs and Symptoms; Patologiska tillstånd, tecken och symtom; Exercise; Träning; Population Surveillance; Populationsövervakning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Occupational Health; Arbetshälsa; Work; Arbete; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Gambling; Spelberoende; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Narcotics; Narkotika; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Education; Utbildning; Occupations; Yrken; Vertigo; Vertigo; Hypersensitivity; Överkänslighet; Feeding Behavior; Ätbeteende; Intellectual Disability; Intellektuell funktionsnedsättning; Violence; Våld; Suntan; Solbränna